2019
DOI: 10.1002/jper.18-0626
|View full text |Cite
|
Sign up to set email alerts
|

Production of interferon‐gamma, interleukin‐6, and interleukin‐1β by human peripheral blood mononuclear cells stimulated with novel lys‐gingipain synthetic peptides

Abstract: Background: Periodontitis is a progressive inflammatory process, and its pathogenesis is related to the presence of a dysbiotic subgingival biofilm that elicits the immune response. Porphyromonas gingivalis is a keystone pathogen, and its Lys-gingipain (Kgp) virulence factor is involved in the pathogen-host interaction through the production of cytokines by host cells, but the specific mechanisms of this interaction have not been elucidated. The present study evaluated the in vitro production of interferongamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Participating in the utilization of heme, the gingipains are also one of the major secreted proteins of P. gingivalis and are an important virulence factor (de Diego et al, 2014;Santos-Lima et al, 2019). Imamura et al (1994) reported that HRgpA and RgpB can accelerate the formation of gingival crevicular fluid (GCF) and the progression of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Participating in the utilization of heme, the gingipains are also one of the major secreted proteins of P. gingivalis and are an important virulence factor (de Diego et al, 2014;Santos-Lima et al, 2019). Imamura et al (1994) reported that HRgpA and RgpB can accelerate the formation of gingival crevicular fluid (GCF) and the progression of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…83,84 Because of its pathogen-related upstream regulation, broad derivation from multiple cell groups and direct effect on immune response and osteoclastic activity, IL-6 was applied widely as a representative pro-inflammatory and damage-related cytokines in in vitro studies and in vivo animal studies and shown to be upregulated after stimulation and downregulated after treatment. [85][86][87][88][89] TNF family TNF was first recognized as a tumour necrotizing substance and named in 1975. 90 The two TNF family members, TNF-α and TNF-β, were purified and identified in the 1980s and share the same membrane receptor.…”
Section: Pro-inflammatory Cytokines Involved In Periodontitismentioning
confidence: 99%
“…32 In another study, cytokine measurement was carried out with the help of ELISA in PBMC stimulated with lysgingipain synthetic peptides belonging to Porphyromonas gingivalis. 33 In the present work, P3 emerged as the most potent candidate, as it was able to induce IFN-γ secretion in all (10) the blood samples followed by P2 ( 7) and P1 (6). Moreover, significant positive correlation was observed between peptide specific cell proliferation and IFN-γ production which jointly represents the potential of these peptides to elicit immune response.…”
Section: Discussionmentioning
confidence: 53%